2009
DOI: 10.1580/1080-6032-020.004.0335
|View full text |Cite
|
Sign up to set email alerts
|

Recreational Surfing Injuries in Cornwall, United Kingdom

Abstract: Surfing injuries were most common in young adult men. Most injuries presenting to the ED were minor/moderate injuries and did not require hospital admission. The overall pattern of injuries was similar to those found in studies from other countries where surfing is popular; however, there was a higher-than-expected incidence of shoulder dislocation. The trends identified in this study could be used to inform education focused on prevention of the most common injuries. Increased use of protective headwear shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 6 publications
2
57
2
Order By: Relevance
“…The most popular location for surfing in the UK is Cornwall, with the highest resident population of regular surfers and a frequent water-sports holiday destination for other UK residents. A study by Hay et al at the emergency department (ED) of the Royal Cornwall Hospital assessed all surfing injuries presenting to Cornwall's emergency services between 2004 and 2006 [6]. They highlighted that for the small proportion of patients with surfing injuries requiring ED treatment (which represented one third of patients and less than 10% of total injuries reported in our study), 90% (n = 190) suffered ''minor or moderate'' injuries only, being discharged following initial ED treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular location for surfing in the UK is Cornwall, with the highest resident population of regular surfers and a frequent water-sports holiday destination for other UK residents. A study by Hay et al at the emergency department (ED) of the Royal Cornwall Hospital assessed all surfing injuries presenting to Cornwall's emergency services between 2004 and 2006 [6]. They highlighted that for the small proportion of patients with surfing injuries requiring ED treatment (which represented one third of patients and less than 10% of total injuries reported in our study), 90% (n = 190) suffered ''minor or moderate'' injuries only, being discharged following initial ED treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Diving into shallow water can cause severe spinal injuries (Beratan and Osborne 1987;Aito et al 2005;Chang et al 2006;Robles 2006;Falcon 2013). Injuries can also result from surfing or body boarding, the latter occurring more frequently in shore break conditions (Nathanson et al 2002;Chang et al 2006; Barucq et al 2009;Hay et al 2009;Meir et al 2011;Falcon 2013), wind surfing (e.g., Kalogeromitros et al 2002) and skim boarding (e.g., Williams et al 2006). Severe injuries can occur from hydrodynamic-driven impact in shallow water while performing some of the aforementioned activities (Chang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that surfing-related injuries happen more often to men ([70 %), with a mean age of the injured population between 25 and 30 years (Barucq et al 2009;Hay et al 2009;Meir et al 2011). Chang et al (2006) separated injuries related to shallow water diving and those associated with hydrodynamic-driven impacts (HDI).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Twenty-six percent of acute surfing injuries are to the head and face and make up 42% of emergency department presentations by surfers. 3 A limited number of small studies have identified the types of acute injuries and chronic pathologies sustained while surfing.…”
Section: Introductionmentioning
confidence: 99%
“…3 A limited number of small studies have identified the types of acute injuries and chronic pathologies sustained while surfing. [1][2][3][4][5][6][8][9][10][11][12][13] There is minimal information in the literature specifically describing the spectrum and mechanisms of head and facial injuries.…”
Section: Introductionmentioning
confidence: 99%